Simulation and Design of Adsorption Ice Maker for Fishing Boat - 王丽伟; 吴静怡; 王如竹; 许煜雄 (Zhileng xuebao)
An adsorption ice-making system driven by exhausted gas of 61610A diesel engine was designed for conserving fish on fishing boats. The system used solidified activated carbon-methanol pair. Simulation and experiments show that heat and mass recovery could enhance the performance of system greatly. The cooling power is 1.93kW when heat and mass recovery is adopted and cycle time is 50min.